Influence of Bi substitution on structural and optical properties of LaFeO\(_{3}\) perovskite - MAHBOUB, Mohammed Sadok; BEN ALI, Ouarda; ZEROUAL, Soria; RIHIA, Ghani; MIMOUNI, Mourad; HAMADNEH, Imad; BAYOU, Samir; BOULAHBEL, Hani; BENARFA, Adel; REHOUMA, Ferhat (Journal of Metals, Materials and Minerals, 2024)
The sol-gel self-ignition method has successfully synthesized a series of homogenous perovskites La1-xBixFeO3 (x=0.0, 0.2, 0.4, 0.6, and 0.8) nanoparticles. Rietveld refinement results from XRD patterns revealed no secondary phases in pure and Bi-substituted LaFeO3 samples. The structural transition from orthorhombic at x = 0.0 until x=0.6 (space group Pbnm) to rhombohedral at x=0.8 (space group R3c) was observed. Lattice parameter values increase slightly with Bi concentration due to the substitution of Bi in the LaFeO3 structure. The average crystallite size D was found to vary between 19 nm and 50 nm. The combination of XRD and SEM demonstrated that the prepared Bi-doped LaFeO3 is a single-phase perovskite with a relatively homogeneous particle size distribution. SEM images revealed quasi-spherical particle shapes. FTIR spectra identify the metal oxide bending vibrations at about 536 cm‒1 and 717 cm‒1 attributed to Fe-O and La-O bonds, respectively. No significant effect of Bi substitution from 0% up to 60% on crystal volume was observed, as confirmed by FTIR spectroscopy, which showed no shift in La/Fe-O bending vibration modes with increasing Bi content. The obtained results indicated that the Eg values exhibited a monotone decrease with an increase in Bi ratio. The band gap values varied from 2.2 eV for pure LaFeO3 to 1.85, 1.76, 1.54 and 1.35 eV for the substitutions of 20%, 40%, 60% and 80% respectively. Hence, the sample La0.2Bi0.8FeO3 with the small band gap value can be used as a promising candidate in solar cell applications.